Up-regulation of Hsp72 and keratin16 mediates wound healing in streptozotocin diabetic rats. Issue 1 (December 2015) - Ahmed, Rasha; Mahmoud, Ayman; Ahmed, Osama; Metwalli, Ali; Ebaid, Hossam
Abstract Background Impaired wound healing is a complication of diabetes and a serious problem in clinical practice. We previously found that whey protein (WP) was able to regulate wound healing normally in streptozotocin (STZ)-diabetic models. This subsequent study was designed to assess the effect of WP on heat shock protein-72 (Hsp72) and keratin16 (Krt16) expression during wound healing in diabetic rats. Methods WP at a dosage of 100 mg/kg of body weight was orally administered daily to wounded normal and STZ-diabetic rats for 8 days. Results At day 4, the WP-treated diabetic wound was significantly reduced compared to that in the corresponding control. Diabetic wounded rats developed severe inflammatory infiltration and moderate capillary dilatation and regeneration. Treated rats had mild necrotic formation, moderate infiltration, moderate to severe capillary dilatation and regeneration, in addition to moderate epidermal formation. Hsp72 and Krt16 densities showed low and dense activity in diabetic wounded and diabetic wounded treated groups, respectively. At day 8, WP-treatment of diabetic wounded animals revealed great amelioration with complete recovery and closure of the wound. Reactivity of Hsp72 and Krt16 was reversed, showing dense and low, or medium and low, activity in the diabetic wounded and diabetic wounded treated groups, respectively. Hsp72 expression in the pancreas was found to show dense reactivity with WP-treated diabetic wound rats. Conclusion This data provides evidence for the potential impact of WP in the up-regulation of Hsp72 and Krt16 in T1D, resulting in an improved wound healing process in diabetic models.